2014
DOI: 10.1144/sp400.37
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation front and oxygen transfer in the fractured zone surrounding the Meuse/Haute-Marne URL drifts in the Callovian–Oxfordian argillaceous rock

Abstract: Deep argillaceous rocks are reducing environments. When exposed to air, reduced minerals of these rocks react with oxygen, modifying the surrounding chemical conditions. Thus, oxidation is an issue in studies about the confining properties of such rocks in the framework of geological disposal projects for radioactive waste. Previous studies in several underground research laboratories (URLs) in argillaceous rocks have shown that oxidation reactions mainly occurred in the excavation-induced fracture network sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Jarosite precipitation is also reported concomitantly with the absence of calcite (De Craen et al, 2008), which is in agreement with the fact that jarosite is an indicator of acidic conditions (Elwood Madden et al, 2012). Other sulfate minerals phases such as celestite, bassanite, and natrojarosite have been observed (Charpentier et al, 2004;Vinsot et al, 2014) as well as precipitation of iron hydroxides. Clay-rocks also contain organic matter (Courdouan et al, 2007;Deniau et al, 2008;Schäfer et al, 2009) that, when oxidized, releases oxygen-functionalized compounds (e.g., carboxyl groups); these compounds might be mobilized by water and participate to further reactions (Faure et al, 1999;Faure and Peiffert, 2007;Blanchart et al, 2012).…”
Section: Perturbing the Physicochemical Conditions In The Subsurface:mentioning
confidence: 99%
See 1 more Smart Citation
“…Jarosite precipitation is also reported concomitantly with the absence of calcite (De Craen et al, 2008), which is in agreement with the fact that jarosite is an indicator of acidic conditions (Elwood Madden et al, 2012). Other sulfate minerals phases such as celestite, bassanite, and natrojarosite have been observed (Charpentier et al, 2004;Vinsot et al, 2014) as well as precipitation of iron hydroxides. Clay-rocks also contain organic matter (Courdouan et al, 2007;Deniau et al, 2008;Schäfer et al, 2009) that, when oxidized, releases oxygen-functionalized compounds (e.g., carboxyl groups); these compounds might be mobilized by water and participate to further reactions (Faure et al, 1999;Faure and Peiffert, 2007;Blanchart et al, 2012).…”
Section: Perturbing the Physicochemical Conditions In The Subsurface:mentioning
confidence: 99%
“…This demonstrates that these are a good path for oxygen transfer. Recently, Vinsot et al (2014) reported on a comprehensive study on oxidized features that have been observed on 115 boreholes cored in the URL (Meuse Haute Marne). Observations were made on cores sampled from a few days earlier to 6.5 years prior with some samples drilled parallel or perpendicular to the horizontal major stress field.…”
Section: Perturbing the Physicochemical Conditions In The Subsurface:mentioning
confidence: 99%
“…Another example of a coupled process is the evolution of redox conditions, a key parameter for RN solubility (Duro et al 2014) which can be modified in connection with hydraulic and mechanical process. The oxidation event that will also occur in the repository near field (Matray et al 2007;Craen et al 2008;Vinsot et al 2013;De Windt et al 2014;Vinsot et al 2014) as result of excavation and ventilation will change redox conditions. These conditions could also been modified if radiological effects are considered.…”
Section: A Need To Consider Coupled Processesmentioning
confidence: 99%
“…This observation is typical when clay rock, containing pyrite, is exposed to air. Indeed, pyrite oxidation enhances the production of hydrogen sulphate released in clay porewater, (Vinsot et al 2014). The oxidation likely occurred between the drilling phase and installation of the equipment.…”
Section: Ic Experimentsmentioning
confidence: 99%